PENGARUH TINGKAT KEPATUHAN WAJIB PAJAK BADAN TERHADAP PENINGKATAN PENERIMAAN PAJAK YANG DIMODERASI OLEH PEMERIKSAAN PAJAK PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MOJOKERTO - Dahnia Wahyu Novitasari; Afifudin Afifudin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to determine and analyze whether there is aninfluence between the level of compliance of corporate taxpayers to increase taxrevenues on Tax Office (KPP) modified tax inspectors. The sample used isprocessed data obtained from Tax Service Office (KPP) from 2015-2017 by usingjudgement sampling. The results of this study indicate that corporate taxpayercompliance has a positive and significant effect on the increase of tax revenuewithout any moderation. Meanwhile, when the occurrence of moderationcompliance has a negative and insignificant effect on tax revenues and taxes havea positive and significant impact on tax revenue.Keywords: corporate taxpayer compliance, tax receipts, and tax audit.